Sikap dan Tingkat Kepuasan Petani akan Introduksi Varietas Unggul Baru Padi Gogo - Chanifah Chanifah; Dewi Sahara; Budi Hartoyo (Institut Pertanian Bogor, 2021)
The development of rice irrigated farming is constrained by the conversion of land agricultural to non-agricultural. Therefore, policy to develop upland rice production in dryland and rainfed lowland is increasingly being implemented. Efforts to expand the application of technological innovations as a lever of upland rice production have intensified by introducing new superior varieties of upland rice. This research aims to analyze farmers' attitudes and satisfaction levels with introducing upland rice to attributes based. The location of this research is in Tegalgiri Village, Nogosari District, Boyolali Regency. Primary data were obtained through a survey method of 35 farmers who planted the Rindang 1, Rindang 2, Inpago 10, and Inpago 12 varieties. Farmer attitudes were analyzed using the Fishbein Multi-attribute Model, while farmer satisfaction level was analyzed using the customer satisfaction index (CSI). The results are the attributes